2013
DOI: 10.1146/annurev-phyto-082712-102321
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. tomato DC3000: A Model Pathogen for Probing Disease Susceptibility and Hormone Signaling in Plants

Abstract: Since the early 1980s, various strains of the gram-negative bacterial pathogen Pseudomonas syringae have been used as models for understanding plant-bacterial interactions. In 1991, a P. syringae pathovar tomato (Pst) strain, DC3000, was reported to infect not only its natural host tomato but also Arabidopsis in the laboratory, a finding that spurred intensive efforts in the subsequent two decades to characterize the molecular mechanisms by which this strain causes disease in plants. Genomic analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
444
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 530 publications
(473 citation statements)
references
References 167 publications
4
444
1
1
Order By: Relevance
“…The T3SS machinery is a filamentous supramolecular structure that provides a channel through which type III effector (T3E) proteins are secreted into the host cells to manipulate host defense responses against bacteria (Büttner, 2016). The first T3SS-associated filamentous structure was discovered in Pseudomonas syringae, a plant pathogen with a broad host range including several important crop species (Jin and He, 2001;Xin and He, 2013;Galán et al, 2014;Büttner, 2016). Our current understanding of detailed molecular and biochemical properties of the T3SS machinery come from studies of human pathogenic bacteria such as Salmonella and Yersinia (Galán et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T3SS machinery is a filamentous supramolecular structure that provides a channel through which type III effector (T3E) proteins are secreted into the host cells to manipulate host defense responses against bacteria (Büttner, 2016). The first T3SS-associated filamentous structure was discovered in Pseudomonas syringae, a plant pathogen with a broad host range including several important crop species (Jin and He, 2001;Xin and He, 2013;Galán et al, 2014;Büttner, 2016). Our current understanding of detailed molecular and biochemical properties of the T3SS machinery come from studies of human pathogenic bacteria such as Salmonella and Yersinia (Galán et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…T3Es are important for the pathogenicity of the bacteria and they play an important role in suppressing the first line of plant defense responses (Xin and He, 2013;Büttner, 2016). Several studies have demonstrated that the effector proteins from pathogenic bacteria are targeted to specific subcellular compartments in cells, where they alter the physiological properties of the cell and suppress innate immunity (Alfano and Collmer, 2004;Kay and Bonas, 2009;Choi et al, 2013;Aung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial pathogen Pseudomonas syringae pv tomato (Pto) and the interaction with its hosts tomato (Solanum lycopersicum) and Arabidopsis thaliana have been intensely studied, and this has significantly enhanced our understanding of plant immunity and microbial pathogenesis (Xin and He, 2013). Plant pathogenic bacteria can deliver 20 to 40 effector proteins into host cells using the type III secretion system.…”
Section: Introductionmentioning
confidence: 99%
“…Most prominently, jasmonate (JA) plays a central role in regulating plant defense against a variety of chewing insects and necrotrophic pathogens, whereas salicylic acid (SA) is critical for plant defense against biotrophic or hemibiotrophic pathogens (1)(2)(3). During host-pathogen coevolution, however, many successful plant pathogens developed mechanisms to attack or hijack components of the plant immune signaling network as part of their pathogenesis strategies (4)(5)(6). As a result, the plant immune system, although powerful, is often fallible in the face of highly evolved pathogens.…”
mentioning
confidence: 99%
“…Because the SA signaling pathway is critical for plant defense against biotrophic and hemibiotrophic pathogens, activation of JA signaling makes plants vulnerable to biotrophic and hemibiotrophic pathogens. In fact, some strains of the hemibiotrophic bacterial pathogen Pseudomonas syringae have evolved an ability to produce a potent JA-mimicking phytotoxin, coronatine (COR), to activate JA signaling as an effective means of inhibiting SA defense and promote plant susceptibility (4,26,28,29). Furthermore, CORlike compounds are produced by pathogens of other taxa (30,31) and proteinaceous effectors from both bacterial and fungal pathogens have been shown to target the COI1-JAZ coreceptor (32)(33)(34).…”
mentioning
confidence: 99%